Systèmes De Mesure De La Performance (SMP) Dans Les PME Marocaines: Les Résultats D’une Recherche Exploratoire - Salwa Bahyaoui (European Scientific Journal, ESJ, 2017)
Despite having experienced profusion since the mid-90s, research on Performance Measurement Systems (PMS) has remained focused on large companies. Interest in the study of such systems in the context of SMEs is not only relatively recent, but occurs mainly in developed countries. This triggered our interest in understanding performance measures in a developing country, namely, Morocco. To do this, an exploratory empirical study was conducted among a sample of Moroccan SMEs. The results, while confirming some specific characteristics of SMEs, help qualify some aspects including those related to the lack of strategic vision and the use of quantitative measures rather than qualitative ones. This paves the way for further research in this area.